Analisis Kemampuan Kognitif Siswa Berdasarkan Taksonomi SOLO pada Materi Sistem Pencernaan Manusia - Dewi Alimah Alya Nabila; Siti Afiah; Nezla Haelila Ainurohmah; Naila Malca Amadia Yusa; Usman Usman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze students' cognitive ability achievement based on the Solo (Structure of the Observed Learning Outcome) taxonomy of digestive system material in class XI. The study used a quantitative descriptive approach with a subject of 28 students. Data collection is done through systematically developed lift instruments to represent five levels of SOLO taxonomy, namely Prestructural, Unistructural, Multistructural, Relational, and Extended Abstract. The data analysis was conducted using descriptive statistics in terms of percentage of achievement, average value, and standard deviation. Research results show that the average student's achievement is high at all levels of SOLO taxonomy, with the highest percentage at the Prestructural level (91.07%) and the lowest at the Relational level (82.14%). Increasing the standard deviation value at a higher cognitive level indicates the heterogeneity of students' ability to integrate and relate concepts coherently. Another interesting finding is the achievement at an Extended Abstract level higher than the Multistructural and Relational levels, indicating the influence of instrument design and problem characteristics on measurement results. Conceptually, the research results show that the mastery of the student's factual knowledge has not been fully accompanied by deep relational understanding. Therefore, this study emphasized the importance of applying constructivist learning approaches, providing conceptual scaffolding, and developing valid and proportional assessment instruments to encourage students' transition to relational and abstract understanding in accordance with the taxonomic hierarchy of SOLO.